Project management step by step : how to plan and manage a highly successful project - Newton, Richard, 1964- (Pearson Education, 2016)
You've been given a project to run. You know you need to get it right, but you don't know what you need to do and in what order to make sure it all runs smoothly and you come out of it looking great. You need Project Management Step by Step. Almost every manager and businessperson finds at some time they need to complete a task that has sufficient complexity and importance that an ad-hoc approach to getting it done is just not enough. Managers in this common situation need the structure and rigour of a project management approach, yet very few managers are formally trained in project man.